Respuesta :
[tex]\displaystyle\\ \sqrt[3]{27a^3b^7} =\sqrt[3]{3^3 a^3b^6\times b} =\sqrt[3]{3^3 a^3\Big(b^2\Big)^3\times b} = \boxed{\bf 3ab^{\b2} \sqrt[\b 3]{\bf b} }\\\\ \text{Correct ansver: a)}[/tex]
Answer:
Option a - [tex]\sqrt[3]{27a^3b^7}==3ab^2\sqrt[3]{b}[/tex]
Step-by-step explanation:
Given : Expression [tex]\sqrt[3]{27a^3b^7}[/tex]
To find : What is the simplest form of expression ?
Solution :
Step 1 - Write the expression
[tex]\sqrt[3]{27a^3b^7}[/tex]
Step 2 - Split the term into their factor,
[tex]27=3^3[/tex]
[tex]b^7=b^3b^3b[/tex]
Step 3 - Re-write the expression,
[tex]\sqrt[3]{27a^3b^7}=\sqrt[3]{3^3a^3b^6b^3b}[/tex]
Step 4 - Simplify the expression
[tex]\sqrt[3]{27a^3b^7}==3ab^2\sqrt[3]{b}[/tex]
Therefore, Option a is correct.